In silico mechanisms of arsenic trioxide-induced cardiotoxicity - Li, Yacong; Wan, Runlan; Liu, Jun; Liu, Weichao; Ma, Lei; Zhang, Henggui (Frontiers in Physiology, 2022)
It has been found that arsenic trioxide (ATO) is effective in treating acute promyelocytic leukemia (APL). However, long QT syndrome was reported in patients receiving therapy using ATO, which even led to sudden cardiac death. The underlying mechanisms of ATO-induced cardiotoxicity have been investigated in some biological experiments, showing that ATO affects human ether-à-go-go-related gene (hERG) channels, coding rapid delayed rectifier potassium current (IKr), as well as L-type calcium (ICaL) channels. Nevertheless, the mechanism by which these channel reconstitutions induced the arrhythmia in ventricular tissue remained unsolved. In this study, a mathematical model was developed to simulate the effect of ATO on ventricular myocyte ionic channels, ventricular myocytes and ventricular tissue by remodeling IKr and ICaL currents. The ATO-dose-dependent pore block model was incorporated into the IKr model, and the promoting degree of ATO to ICaL was estimated based on experimental data. Simulation results indicated that ATO extended the action potential duration of three types of ventricular myocytes (VMs), including endocardial cells (ENDO), midmyocardial cells (MCELL), and epicardial cells (EPI), and exacerbated the heterogeneity among them. ATO could also induce alternans in all three kinds of VMs. In ventricular cables, the side effects are reflected in a prolonged QT interval of ECG and a wide vulnerable window, thus increasing the possibility of spiral wave formation in ventricular tissue. In addition to verifying that ATO induced long QT syndrome, we revealed that the heterogeneity caused by ATO is also an essential hazard factor. Based on this, a pharmacological intervention of ATO toxicity by resveratrol was undertaken. This study provides a further understanding of ATO-induced cardiotoxicity, which may help to improve the treatment regimen for APL patients.